Evaluación de la acción de biocontroladores de cepas de Bacillus subtilis y Trichoderma spp e Hidrolato de ciprés frente a la Ralstonia solanacearum en plántulas de Eucalyptus urograndis en la Hacienda San Fernando, propiedad de NOVOPAN del Ecuador S.A - Caisa Melendrez, Cristopher Cesar (2021)
Worldwide, Eucalyptus spp. plantations have been increasing and with this the sanitary problems have increased. Among them we have the bacterial wilt caused by the bacterium Ralstonia solanacearum, which once infected the plant will hardly survive. For this reason, we have opted for prevention through the application of bio-controllers directly to the plants and soil where the bacterium is hosted. The objective of this research was to determine the action of biocontrol strains of Bacillus subtilis, Trichoderma spp and cypress hydrolate against R. solanacearum in Eucalyptus urograndis seedlings at San Fernando Farm, property of NOVOPAN del Ecuador S.A. An experimental design with completely randomized blocks was carried out. With a block distribution in the field and applying three base treatments and a control. A soil sample was taken from each completely randomized block, each sample weighing approximately 200 grams. The seedlings were established with their respective treatments. Data collection was carried out monthly until the third month. Samples of plant tissue (stem, leaves, apices) that were still green were collected from all the treatments arranged in the three blocks. The Elisa test was used to detect R. solanacearum. For the statistical analysis, an ANOVA was performed with the INFOSTAT program to determine which of the treatments showed positive results in growth and in the absence of phytosanitary problems. As a result, the block with the highest concentration of R. solanacearum was block three with 124000 CFU/gr, followed by block two with 113500 CFU/gr and block one with only 12000 CFU/gr. In addition, the seedlings which were subjected to treatment three (cypress hydrolate) showed a greater increase in height (49.66) and diameter at the root collar (7.54 mm). Treatment three (cypress hydrolate) was the best in stimulating seedling growth and protected against other pathogens, thus showing the least number of seedlings with phytosanitary problems. Key words: Biocontrollers, Ralstonia, Bacillus, Trichoderma, Hydrolate.